STABILITAS WARNA DAN PERUBAHAN pH WEDANG UWUH SIAP MINUM SELAMA PENYIMPANAN - Septiyani, Retnosyari; Rahayu, Wahidah Mahanani; Permadi, Adi (Universitas PGRI Semarang, 2024)
Wedang uwuh is a traditional drink from Yogyakarta with various product forms. Ready-to-drink wedang uwuh is a more practical and economical alternative for consumption, but with limited color stability around 1 day. This research aims to examine the color stability of ready-to-drink wedang uwuh at varying temperatures and brewing times, at room and cool temperature, and with sugar or Na-benzoate addition. The experiment was carried out in a Completely Randomized Design with a variety of brewing conditions of temperature (75°C, 85°C, and 95°C) and time (10, 15, and 20 minutes) at material and water ratio of 1:1 (wv), followed by filtration and storage. The filtrate was then observed for changes in color for 7 days. Brewing condition with best color stability at 85oC for 20 minutes were then treated with the addition of sugar or sodium benzoate and then tested for pH and color for 9 days storage in cool and room temperature. The research results showed that all samples (original, sugar added, and Na-benzoate added) had pH color change during storage, but original and Na-benzoate added had the best stability. Ready-to-drink wedang uwuh stored in cold temperature had better red color stability than room storage.